Technological and economic dynamics of a Brazilian ceramic tiles cluster - Machado, Solange A.; Plonski, Guilherme Ary; Filho, João Pizysieznig (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This paper proposes a general model to explain de birth and evolution of industrial clusters that could contributes not only with the phenomenon knowledge but also to public policies and private strategies fundamentals. The model was validated with the case of Santa Gertrudes' cluster, which produces ceramic tiles in São Paulo State.The main hypothesis is that a revolutionary innovation, combined with specific local conditions, is the very origin of a new cluster. In this model, an industrial cluster presents an evolutionary cycle that encompasses embryonic, growth, and maturity phases, each phase having distinctive competitive patterns. The Santa Gertrudes' cluster had an evolutionary trajectory as predicted by the model. The cluster was born of a process innovation and developed specific trajectories in each phase. Nowadays, the cluster is passing through the turning point from the growing phase to the maturity phase. © 2007 PICMET.